(untitled) (Bangladesh Journal of Livestock Research, 2020)
The present study was conducted at Bangladesh Livestock Research Institute, Savar, Dhaka to assess the performances of three Indigenous Chicken genotypes under intensive management. A total of 1128-day-old chicks comprising of 3 types of chicken namely Naked Neck (NN), Hilly (H) and Non-descript Deshi (ND) were hatched in one batch for this study. Significant (p<0.001) body weight differences among the genotypes were observed at 12th and 16th weeks of age, with the highest body weight observed for H genotype (1250.71±27.71, and 1502.54±36.81g) among the other two genotypes. NN genotype (2.85%) had significantly higher chick mortality than ND (0.68 %) and H (2.08 %) genotypes at 0-8 weeks of age. The age at first egg laid was significantly (p<0.001) affected by genotype. The age at which Indigenous Chickens start laying eggs ranged from 152.79 to 161.95 days. The Hen-day egg production (HDEP%) observed in the present study were affected significantly (p<0.001) by genotype. In this study, the average HDEP% of ND, H and NN were found to be 38.44±2.18, 30.43±2.10 and 41.95±2.11. Eight week body weight of males ND, H and NN birds were expected to increase by 64.7, 46.1 and 43.9g, respectively. While in females ND, H and NN birds, the expected responses were 21.5, 27.9 and 10.7g, respectively Bangladesh J. of Livestock Res. 21-25: 153-158, 2018